Annals Graphic Medicine - I'll Heal Myself - Councilor, KC (Annals of Internal Medicine, 2024)
Keywords: dept.com

Gendered bodies: A graphic medicine commentary - Barry Councilor, K.C.; Fink, A.E. (Social Science and Medicine, 2024)
This final commentary, in comic format, frames this special issue using Graphic Medicine methodologies to explore broader themes and meanings related to the scientific study of gender and health. Comics can be seen as a way to introduce complex human narratives and as an exploratory tool to ask broader social-contextual and ethical questions about health and medicine. This piece is also constructed through the lens of queer scholarship, which, together with the comics format, provides opportunities to build more embodied, complicated narratives about gender, sexuality and health. Most importantly, comics are used as a modality to tell compelling narratives about how individuals, rather than populations, may be impacted by biomedical conceptualizations of gender and health. The commentary includes a series of graphic narratives containing hypothetical stories and cases: stories of how individuals may be harmed within healthcare systems by rigid framings of gender, sex and sexuality, and stories about how gender socialization may impact health in subtle ways. These narratives furthermore examine the inextricable link between gender and power, illustrating how overt and covert manifestations of power may shape a person's health over the life course. Finally, the piece explores how expansive views of gender may contribute to positive health care experiences. The intention of this piece is to nudge scientific researchers and clinicians alike to approach the topic of gender, sexuality and health with nuance and curiosity. © 2023 The Author(s)
Keywords: Comics; Embodiment; Gender; Gender-affirming care; Graphic medicine; Health; Narrative; Power; Sex; Sexuality; Transgender; Trauma; dept.com; peer-reviewed